Tjurkizmy v toponimii Ukrainy - Lučyk, Vasyl' V. (Linguistica (Ljubljana), 2015)
The centuries-old contact of Turkic tribes with the native population of Ukraine is broadly reflected in Ukrainian toponymy where Turkisms are one of the largest groups among foreign place names. They embedded into the native speech during three main periods: 1) the Kievan Rus (Ancient Ukrainian) period - 9-13th century (...); 2) the Old Ukrainian period - 14-18th century (...); 3) the New Ukrainian (Modern) period - 19-21st century (...). The etymology of Turkic toponyms reflects the following: inherent properties of geographical elements (...); relations of the elements denoted to other (mainly adjacent) surrounding elements (...); relation to people (city of Izmail < male name Ismail as former attributive in the Ezafe construction). Derivatives of each of these toponymic principles may be used to express cultural and historical values or religious aspects (...) that may permeate Ukrainian contact speech (compare the name of the town Pyatykhatky that came into use under the Turkic cultural influence). In the last (Modern) period, the Turkic influence on the geographical names remained mainly in Slavicized Crimea where the toponyms were for the most part of Crimean Tatar origin. However, in the Soviet time the majority of foreign names (principally oikonyms and urbanonyms), including Turkic ones, on the peninsula as well as in the whole of the Ukraine were deliberately changed.
Keywords: etimologija; étymologie; etymology; toponymes; turcismes; turkizmi; Ukraine; Ukrajina; zemljepisna imena